Multiple Giant Cerebral Hydatid Cysts in Pediatrics - Dagnachew Yohannes Gechera; Murtii Teressa Obolu; Abdulaziz Abdellah Hussein; Yared Assefa Beyene; Tadesse Getachew Mulisa; Kibrom Legesse Abrha (Clinical Case Reports)
ABSTRACT In Ethiopia, although multiple giant cerebral hydatid cysts are rare, rural children in close contact with dogs remain at risk. Diagnosis requires clinical suspicion and advanced imaging. Dowling hydrodissection allows intact cyst removal. Preoperative anthelmintics minimize allergic risks. Early Surgical intervention improves neurologic recovery, and follow‐up is essential for potential recurrence.